From the Orbit of the Generation of 27 to Surrealism. The Case of Intimate Being by José María de la Rosa - Martín Fumero, José Manuel (2021)
José María de la Rosa is one of the authors of the avant-garde island lyric whose scriptural evolution, like other contemporary authors such as Agustín Espinosa, Domingo López Torres, Emeterio Gutiérrez Albelo or Pedro García Cabrera, started from the last aesthetic, that of 27, up to surrealism. This article aims to critically besiege his first work, Intimate Being (1936), a poetry book hardly studied and of whose content there are hardly any references. We will carry out an analysis of textual criticism based on the original texts published by the author, studying both its thematic and expressive aspects, in order to relate it to the aforementioned authors, amen with other names from 27 whose reading nurtured his creative process. As a result, it will be appreciated that the aesthetics of ‘27 was a necessary learning to finally lead to the surreal torrent.